2013
DOI: 10.1021/ct400282h
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Sampling by Ab Initio Molecular Dynamics Simulations Improves NMR Chemical Shift Predictions

Abstract: Car-Parrinello molecular dynamics simulations were performed for N-methyl acetamide as a small test system for amide groups in protein backbones, and NMR chemical shifts were calculated based on the generated ensemble. If conformational sampling and explicit solvent molecules are taken into account, excellent agreement between the calculated and experimental chemical shifts is obtained. These results represent a landmark improvement over calculations based on classical molecular dynamics (MD) simulations espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 80 publications
3
38
0
Order By: Relevance
“…Dračínský et al also encourage using predicted NMR chemical shifts as a way of evaluating new MD force fields. In their study comparing ab initio MD and classical MD for dynamic averaging, they found that ab initio MD allowed for better conformational sampling, especially for N‐H distances.…”
Section: Conformational Averagingmentioning
confidence: 99%
“…Dračínský et al also encourage using predicted NMR chemical shifts as a way of evaluating new MD force fields. In their study comparing ab initio MD and classical MD for dynamic averaging, they found that ab initio MD allowed for better conformational sampling, especially for N‐H distances.…”
Section: Conformational Averagingmentioning
confidence: 99%
“…Solely conducting MD simulations and taking a few snapshots for the DFT‐based NMR parameter calculation as proposed by Kwan and Liu23 (see also Ref. 24) does not solve the problem either because a proper average cannot be obtained in this way with reasonable effort, and furthermore, somewhat higher but still thermally accessible barriers (5–10 kcal mol − 1 ) are very difficult to overcome. A very important “side product” of our procedure is that in case of a reasonable coincidence of experimental and theoretical spectra, knowledge of the dominantly contributing conformers under the measurement conditions is obtained.…”
mentioning
confidence: 99%
“…The calculated isotropic shielding constants were averaged over all sampled configurations and subtracted from the corresponding shielding constant of tetramethylsilane (TMS) computed at the same QM level of theory. 125,126 In this way, the combined effects of solvent and its influence on the local geometry of the G-quadruplex, on calculated chemical shifts, are taken into account. For comparison, we have also carried out analogous calculations based on configurations obtained by classical optimization at the AMBER MM level and for the X-ray structure.…”
Section: Resultsmentioning
confidence: 99%